Association of Urinary Incontinency with COPD Severity: An Analytical Cross-sectional Study : Urinary Incontinency and COPD Severity - Lashari, Asma; Irfan, Umama; Hamid, Khizra; Munawar, Raheel; Salik, Sumbal; Mushtaq, Zeeshan; Khalid, Amna (Pakistan Journal of Health Sciences, 2024)
Large number of patients suffers from urinary incontinence (UI) with COPD leading to urine leakage and affecting their quality of life. Objective: To determine the prevalence and association of UI among with the severity of COPD patients. Methods: The cross sectional study was conducted from February 2023 to June 2023 in Ghurki Teaching Trust Hospital, Shalimar Hospital and Gangaram Hospital. 230 male patients of age 45-65 years suffering with COPD were selected by using convenient sampling technique. The demographic data and International Consultation on Incontinence Questionnaire- Urinary Incontinence Short Form (ICIQ-UI SF) were used collected. SPSS version 26.0 along with Chi-square was used for analysis with p-value <0.05. Results: The results showed that 36 (15.7%) suffering with mild COPD, 142 (61.7%) had moderate COPD and 52 (22.6%) had severe COPD in which 33 (14.3%) experience have no urine incontinency, 25 (10.9%) had urge Incontinence, 154 (67%) had stress Incontinence and 18 (7.8%) had mixed Incontinence. Additionally; moderate COPD had shown significant association with stress incontinency with Chi-square value of 188.58 and p-value =0.00 and with the leakage of urine on coughing/ sneezing, during any physical activity/ exercise and all the time with value of 143.37, p-value = 0.00. Conclusions: The study concluded that UI is highly prevalent in COPD patients as stress and urge incontinency is highly prevalent among moderate and severe patients respectively, associated with coughing/ sneezing and physical activity/ exercises.